Effect of packaging materials and storage conditions on the degradation of xanthophylls in yellow-maize ogi powder - Awoyale, W.; Maziya-Dixon, B.B.; Alamu, Emmanuel Oladeji; Menkir, A. (2016)
The need to evaluate the effects of packaging materials and storage conditions on the degradation of xanthophylls in yellow maize ogi powder is important due to its health implication. Ogi powder was packaged in high-density polyethylene bag (HDPE), polypropylene woven sack (PP), and polyvinyl chloride container (PVC). The samples were stored under different conditions for 12 weeks and sampled at three-week intervals for analysis using High Performance Liquid Chromatography. The result showed that the total xanthophyll content of the ogi powder was 10.39 µg/g before storage with of zeaxanthin having the highest value (6.73 µg/g) and lutein (3.66 µg/g) the least. The reduction in lutein and zeaxanthin contents was significant in the ogi powder packaged in HDPE stored at 35°C and 50% relative humidity (RH). Therefore, PVC is recommended at 34°C and RH of 54% for up to 6 weeks while HDPE may be used at 28°C and 68% RH for 9 weeks, and that of PP might be 35°C and 50% RH if the storage period is extended to 12 weeks.